Outer Membrane Vesicles of Bacteria - Chatterjee, S.N.; Chaudhuri, Keya.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book provides a detailed account of the physico-chemical properties and biological functions of the outer membrane vesicles (OMVs) of different pathogenic and non-pathogenic Gram-negative bacteria. It also includes an authentic record of the first systematic study that discovered the mechanism of OMV formation by a pathogen, Vibrio cholerae, and proposed that the process represented a novel secretory activity of bacteria. Furthermore, the authors present clinical and laboratory data on the use of OMVs as immunogens, as effective and licensed vaccines against Neisseria meningitidis serogroup B infections and on the development of more effective vaccines against other human and animal pathogens including Vibrio cholerae. This volume thus bears witness to the emerging revolution in the field of vaccines against pathogens and closes with a discussion of open questions and future research on OMVs.
Discovery of outer membrane vesicles: A revisit to the contemporary works -- Gram-negative bacteria: The cell membranes and the outer membrane vesicles -- Factors affecting production of outer membrane vesicles -- Outer membrane vesicles as carriers of biomaterials -- Outer membrane vesicles and the biofilm formation -- Outer membrane vesicles: Interaction with prokaryotes and eukaryotes -- Biogenesis of outer membrane vesicles -- Release of outer membrane vesicles: Is it a novel secretion mechanism ?- Outer membrane vesicles: Physiological and medical applications -- Concluding notes.
Keywords: Medicine; Immunology; Microbiology; Cell membranes; Bacteriology; Biomedicine; Medical Microbiology; Immunology; Bacteriology; Membrane Biology